Coping with violence in the new testament - De Villiers, Pieter; Van Henten, Jan Willem (Leiden : BRILL, 2012)
The present publication aims to contribute to the recent scholarly debate about the interconnections between violence and monotheistic religions by analysing the role of violence in the New Testament as well as by offering some hermeneutical perspectives on violence as it is articulated in the earliest Christian writings.
Religion, Bible and violence / Jan Willem van Henten -- Violence in the New Testament and the Roman Empire: Ambivalence, othering, agency / Jeremy Punt -- Paul's version of "turning the other cheek": Rethinking violence and tolerance / Andries van Aarde -- Violence in the Letter to the Galatians? / Francois Tolmie -- A godfighter becomes a fighter for God / Rob van Houwelingen -- Jesus and violence: an ideological-critical reading of the tenants in Mark 12:1-12 and Thomas 65 / Ernest van Eck -- The use of violence in punishing adultery in biblical texts : (Deuteronomy 22:13-29 and John 7:53-8:11) / Wim J.C. Weren -- Violence in a gospel of love / Jan van der Watt and Jacobus Kok -- Images of war and creation, of violence and non-violence in the Revelation of John / Paul B. Decock -- Unmasking and challenging evil: Exegetical perspectives on violence in Revelation 18 / Pieter G.R. de Villiers -- The eschatological battle according to the book of Revelation: Perspectives on Revelation 19:11-21 / Tobias Nicklas -- Hermeneutical perspectives on violence in the New Testament / Pieter G.R. de Villers.
Print version record.
Includes bibliographical references (pages 275-294) and indexes.
Master record variable field(s) change: 072
Keywords: Bible. -- Criticism, interpretation, etc. -- Congresses; Bible; Violence -- Religious aspects -- Christianity -- Congresses; Violence in the Bible -- Congresses; Religion; RELIGION -- Biblical Studies -- New Testament; Religion; Violence in the Bible; Violence -- Religious aspects -- Christianity; Electronic books; Conference papers and proceedings; Criticism, interpretation, etc